ANALYSIS OF THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CLIMATE ON EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Nisbayanti; Mardiana Y, Ria; Hakim, Wardhani (Accounting Profession Journal (APAJI), 2024)
This study aimstoprobehowTransformationalLeadershipandOrganizationalClimateaffectEmployee Performance ofworkersofthe Regional Drinking Water Company(PDAM) in Makassar City throughOrganizationalCitizenshipBehavior(OCB) variables. This study usesanalyticobservationalwith a Cross-Sectionaldesign. The populationofthis study are endlessfieldworkers, totaling 351 workers. Pulloutofsamplesusingprobability sampling usingsimplerandom sampling, sothatthenumberofsamples in this study amountedto 237 respondentsattainedusingthe Slovin formula. The data analysisused in this study isthePartialLeastSquare(PLS) approach. The resultsshowedthatTransformationalLeadership had a positivebut not significanteffectonOrganizationalCitizenshipBehavior(OCB) in PDAM Makassar City, OrganizationalClimate had a positiveandsignificanteffectonOrganizationalCitizenshipBehavior(OCB), TransformationalLeadershippositiveandsignificanteffectonEmployee Performance, OrganizationalClimate has a positiveandsignificanteffectonEmployee Performance, OrganizationalCitizenshipBehavior(OCB) has a positiveandsignificanteffectonEmployee Performance, TransformationalLeadership has a positiveandsignificanteffectonEmployee Performance intermediatebyOrganizationalCitizenshipBehavior(OCB), OrganizationalClimate has a positiveandsignificanteffectonEmployee Performance intermediatebyOrganizationalCitizenshipBehavior(OCB)